Technical aspects in dairy biogas production - Silveira, José Luz; Villela, Iraídes Aparecida de Castro (Revista Ciências Exatas, 2008)
This paper presents initially some historical aspects of biogas production and shows the two most used biodigestors in Brazil: Batching or Discontinuous Biodigestors and Continuous Biodigestors, utilized for the biomass fermentation. Afterwards, the biogas production of a medium-size Dairy located in the Paraíba Valley is described and detailed. In this plant, the biogas average production is 80 Nm3/h with inferior heat power of 22,475.80 kJ/Nm3. This energetic good is produced from the organic material (wastes) decomposition deriving from the milk and milk Products production process, which are sent from the productive process to the Wastewater Treatment Plant (WTP). Its experimentally measured mol composition is: 62.7% CH4, 3.4% CO2, 2.4% H2O and 14.1% H2S. This work aims to verify the biogas production generated by milky product fermentation in the WTP. It can be concluded that through fermentation of milky products a large biogas production is obtained, which should be used as an energy source for the studied plant (VILLELA, 1998).